Sävelten tyttäret Säveltävät naiset Suomessa 1800-luvulta 1900-luvulle - Välimäki, Susanna (Historiallinen Arkisto, 2023)
The book presents the biographies and work lists of 126 Finnish women composers born between 1784 and 1909. Based on large-scale archival research, it is the first comprehensive historical account of Finnish women composers and their cultural heritage. The authors draw on feminist music history and the sociohistorical approach to find out who these women were, what kind of music they wrote, and how their careers reflected European cultural and social history. The treatise highlights the influence of girls' schools, women's suffrage movements and other socio-political developments on the musical culture of women. Concepts such as "composer", "woman" and "Finnish" were assumed to be open and inclusive throughout the research, in terms of both musical style and diversity in cultural background. In concentrating on music-making by women, the book opens up radically new vistas on Finland's music and cultural history, and it rectifies previous erroneous conceptions about women's composership and their artistic work. In short, it exposes the richness in the sonic and intellectual heritage of Finnish women composers, as well as its significance in society today.